Diversitas Gender Dewan Direksi, Risiko, dan Kinerja Perusahaan - Rahmat Setiawan; Ninditya Nareswari; Putu Ayu Indira Savitri Suryana (Jurnal Mirai Management, 2022)
Issues related to board directors have attracted the interest of various research. Gender diversity in board of director is believed to affect firm’s risk and performance in several ways. This study aims to understand the impact of gender diversity in board of director on firm risk and firm performance. Firm risk in this research are total risk and systematic risk. Total risk is measured by deviation standard of daily return, Systematic risk is measured by beta, and performance is measured by Tobin’s Q. The author uses 87 samples of non-financial firm in Indonesia during 2011-2014 with 155 observations. Based on this research, the result of multiple linear regression showed that gender diversity in board of director has a significant negative effects on firm risk and significant positive effects on firm performance. This means that the firms with greater gender diversity in board director show lower risk and deliver better performance. Keywords: Gender Diversity, Risk, Performance, Board of Director